Open volumetric air receiver: An innovative application and a major challenge. Issue 1 (29th April 2021) - Kumar, Vishwa Deepak; Upadhyay, Vikas K.; Singh, Gurveer; Mukhopadhyay, Sudipto; Chandra, Laltu
Abstract: The open volumetric air receiver (OVAR) based systems can be used for metals processing operation, such as, the heat treatment of aluminum. Some important aspects, related to the technology adaptation, are (a) the selection of receiver design, (b) the integration of an application, based on hot air, with an OVAR, and (c) mitigation of dust deposition in the porous absorber of an OVAR. Therefore, the presented aspects are (a) literature review on the porous absorbers for OVARs, (b) literature review on solar furnace, and an innovative OVAR‐based solar convective furnace (SCF) for the heat treatment of aluminum, and (c) mechanism of transport and deposition of dust in an absorber pore. These reveal that (a) the design improvements are required, to enhance the thermal efficiency of OVARs, for an input power to air mass flow rate ratio exceeding 900 kJ/kg, (b) the SCF system, based on OVAR, is plausible, and (c) the dust deposition in an absorber pore may be mitigated. The findings will be useful for deployment and operation of the OVAR based systems in arid deserts. This article is categorized under: Solar Heating and Cooling > Science and Materials Abstract : (a) A schematic of solar convective furnace system, (b) the installed solar air tower simulator facility, (c) an OVAR design, and (d) dust transport and deposition in an absorber pore. ​